The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/jvh.12572
|View full text |Cite
|
Sign up to set email alerts
|

Maternal anti‐HBVs suppress the immune response of infants to hepatitis B vaccine

Abstract: It is still controversial whether maternal anti-HBV antibodies (anti-HBVs) affect the infants' immune response to hepatitis B virus (HBV) vaccination. This multicentre study aims to address this question. First, we determined whether the transplacental transfer of maternal anti-HBVs occurs by measuring the titres of 90 anti-HBVs-positive pregnant women and their newborns. The anti-HBVs-positive rates of newborns ranged from 89.7% to 100.0%, depending on the maternal anti-HBVs titres. Secondly, we investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
(45 reference statements)
0
4
1
Order By: Relevance
“…There have been suggestions that HBV antigens/antibodies can influence the immune response of infants to hepatitis B vaccine . In our study there were no significant differences in anti‐HBs levels between HBV‐exposed and unexposed infants although at 24 months there was a trend towards a lower level in the HBV‐exposed suggesting that further data are needed to determine if different strategies are needed for these infants.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…There have been suggestions that HBV antigens/antibodies can influence the immune response of infants to hepatitis B vaccine . In our study there were no significant differences in anti‐HBs levels between HBV‐exposed and unexposed infants although at 24 months there was a trend towards a lower level in the HBV‐exposed suggesting that further data are needed to determine if different strategies are needed for these infants.…”
Section: Discussioncontrasting
confidence: 58%
“…This is particularly important for infants born to HIV‐positive mothers in whom a decreased response could be observed and in whom HBV transmission may more frequently occur due to high HBV‐DNA levels in co‐infected mothers . Maternal HBV co‐infection could also be potentially associated with a lower response to HBV vaccine since maternal specific antibody can interfere with the infant's own response to vaccination …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For live measles vaccine, vaccination in the context of passive immunity is known to dampen the specific humoral response to vaccination [31]. Such attenuating effect of maternally-derived antibodies on human infant humoral vaccine responses has also been observed for the non-live viral vaccines inactivated polio vaccine [32] and hepatitis B vaccine [33], and this is corroborated by a series of animal experimental studies [31], including studies in pigs of non-live Haemophilus parasuis immunization [34]. In humans and pigs alike, the development of active cellmediated immunity may not be compromised by the presence of maternal immunity despite blunted humoral responses, as observed for Mycobacterium hyopneumoniae vaccination of piglets from immunized dams [35] or live measles vaccine in humans [31].…”
mentioning
confidence: 88%
“…A large multicenter study by Chen et al of 1,063 mothers who were HBsAg−/anti‐HBs+ and their infants showed a strong negative correlation between maternal anti‐HBs and infant anti‐HBs titers in vaccinated infants. Further, up to 23% of infants born to mothers with protective anti‐HBs titers >10 IU/L did not respond to the standard vaccination series.…”
Section: Epidemiology Of Hbv and Mtctmentioning
confidence: 99%